The Role of Service Quality in Santri Satisfaction at the Darussalam Islamic Boarding School Cooperative, Tanjung Jabung Timur Regency - Setiawan, Agus; Wargo; Wulandari, Triyana (Zabags International Journal of Economy, 2025)
The increasing demands of society on educational institutions to produce high-quality future generations have pushed Islamic boarding schools (pesantren) to integrate not only religious education but also economic empowerment through cooperative enterprises. This study aims to explore the role of service quality in influencing santri satisfaction within the Darussalam Islamic Boarding School Cooperative in Tanjung Jabung Timur Regency. Using a qualitative approach with a case study strategy, the research collected primary data through observation, interviews, and documentation involving santri who had made repeated purchases. The findings reveal that the cooperative plays a dual role as both a provider of essential goods and a platform for entrepreneurial education. Empathy, responsiveness, and reliability emerged as key service quality dimensions contributing to customer satisfaction. However, the study also identified structural limitations such as inconsistent service procedures and inadequate facilities. These results highlight the significance of aligning service quality with Islamic values and educational goals to enhance both satisfaction and institutional effectiveness. The study contributes to the literature by contextualizing service quality within faith-based educational settings and offers practical recommendations for strengthening cooperative operations in pesantren environments.